Management of labor behavior of employees as a factor of economic security of the organization - M. B. Zhernakova; T. Yu. Krotenko (Вестник университета)
As a result of changes in the sectoral structure ofproduction, applied technologies ofproduction and management of organizations in the total social work is constantly increasing the proportion of mental labor. At present, the assessment of workers, engaged in mental work, is traditionally carried out on the basis of indicators of their labor activity. Labor activity characterizes mainly the economic behaviour of the employee, reflects the quantitative results of his labor. At the same time, many of the activities and operations of mental nature are not amenable to accurate planning and adequate quantitative assessment. Therefore, in the management of employees of mental labor, it is necessary to focus on a group of methods, regulating not labor activity, but labor behavior of workers.